2023
DOI: 10.4018/jgim.326763
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Challenges in Developing and Managing Digital Agility Among Sri Lankan Family Business Owners During the Economic Crisis Situation

Abstract: The purpose of this qualitative study is to explore the ongoing post-pandemic challenges in developing and managing digital agility among Sri Lankan family business owners. This study used a mono-method qualitative approach to identify the management strategies using the self-determination theory and social exchange theory to cope with digital agility among Sri Lankan family business owners. Authors interviewed 25 family business owners in Sri Lanka and assessed the findings using the NVivo software. A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…Employing protection-motivation theory and the theory of planned behavior, Marshall et al (2022) found that self-efficacy had a significant direct impact on security-behavior intention and an indirect impact on security behavior among university students. Response cost is the estimated physical and psychological cost (e.g., in time, money, and effort) of performing a protective behavior (Ezati Rad et al, 2021;Jayawardena et al, 2023;Taheri-Kharameh et al, 2020), overcoming a complex problem, or controlling a powerful habit (Haag et al, 2021). Both self-efficacy and response cost have a great impact on behavioral intention (Farooq et al, 2019;Hsu & Lee, 2023;Lee & Seomun, 2021;Maddux & Rogers, 1983;Marikyan & Papagiannidis, 2023;Marshall et al, 2022).…”
Section: Protection-motivation Theorymentioning
confidence: 99%
“…Employing protection-motivation theory and the theory of planned behavior, Marshall et al (2022) found that self-efficacy had a significant direct impact on security-behavior intention and an indirect impact on security behavior among university students. Response cost is the estimated physical and psychological cost (e.g., in time, money, and effort) of performing a protective behavior (Ezati Rad et al, 2021;Jayawardena et al, 2023;Taheri-Kharameh et al, 2020), overcoming a complex problem, or controlling a powerful habit (Haag et al, 2021). Both self-efficacy and response cost have a great impact on behavioral intention (Farooq et al, 2019;Hsu & Lee, 2023;Lee & Seomun, 2021;Maddux & Rogers, 1983;Marikyan & Papagiannidis, 2023;Marshall et al, 2022).…”
Section: Protection-motivation Theorymentioning
confidence: 99%
“…External knowledge search is also guided by routines, but past routines are based on historical experience, not rational decision-making. Lagging routines cause big data firms to have difficulty guaranteeing the efficiency and efficacy of external knowledge search behavior in the knowledge economy and digital era (Jayawardena et al, 2023;Yang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have recognized the relevance of digital agility in an era where technology is altering various aspects of life, including work, thinking, learning, collaboration, and communication, all aimed at remaining competitive and relevant in the surrounding context (Salmela et al, 2022;Troise et al, 2022). Overall, possessing digital agility is essential in today's fast-paced digital world, offering an advantage in navigating the ever-shifting digital landscape (Troise et al, 2022;Jayawardena et al, 2023). However, there are three main gaps in the literature:…”
Section: Introductionmentioning
confidence: 99%